Allotment garden dwellings - Lorbek, Maja (Urbani izziv, 2015)
At the end of 19th century, the removal of city walls and introduction of mass transport in European cities provided the opportunity to expand cities in green suburban areas. Colonies of small houses with garden plots and allotment gardens developed during this era thus represent a new type of settlement, where green infrastructure (gardens) and allotment dwellings are closely intertwined. The gardens in these settlements were originally based on the notion of subsistence economy, providing food and emergency accommodation in periods of crisis. This paper examines the evolution of allotments and particularly allotment dwellings in Germany and Austria by matching the actual practices of gardeners with the formation of and changes in the legal framework. The legislation and zoning regulations, which were predominantly established after the fact, reveal an ongoing process of negotiation between informal practices and planning authorities.
Keywords: allotment dwelling; allotment gardens; ecosystem services; informal practice; legal framework; mesta; spatial planning; vrtovi; zakonodaja